CRYPTOCHROME 1a-mediated blue light perception regulates tomato seed germination via changes in hormonal balance and endosperm-degrading hydrolase dynamics - de Oliveira, Reginaldo [UNESP]; Alves, Frederico Rocha Rodrigues; da Rocha Prado, Emilaine [UNESP]; Gomes, Letícia Danielle Longuini; Freschi, Luciano; Gaion, Lucas Aparecido; Carvalho, Rogério Falleiros [UNESP] (Springer Nature, 2023)
Main conclusion: Blue light exposure delays tomato seed germination by decreasing endosperm-degrading hydrolase activities, a process regulated by CRY1a-dependent signaling and the hormonal balance between ABA and GA. Abstract: The germination of tomato seeds (Solanum lycopersicum L.) is tightly controlled by an internal hormonal balance, which is also influenced by environmental factors such as light. In this study, we investigated the blue light (BL)-mediated impacts on physiological, biochemical, and molecular processes during the germination of the blue light photoreceptor CRYPTOCHROME 1a loss-of-function mutant (cry1a) and of the hormonal tomato mutants notabilis (not, deficient in ABA) and procera (pro, displaying a GA-constitutive response). Seeds were germinated in a controlled chamber in the dark and under different intensities of continuous BL (ranging from 1 to 25 µmol m−2 s−1). In general, exposure to BL delayed tomato seed germination in a fluency rate-dependent way due to negative impacts on the activities of endosperm-degrading hydrolases, such as endo-β-mannanase, β-mannosidase, and α-galactosidase. However, not and pro mutants presented higher germination speed index (GSI) compared to WT despite the BL influence, associated with higher hydrolase activities, especially evident in pro, indicating that the ABA/GA hormonal balance is important to diminish BL inhibition over tomato germination. The cry1a germination percentage was higher than in WT in the dark but its GSI was lower under BL exposure, suggesting that functional CRY1a is required for BL-dependent germination. BL inhibits the expression of GA-biosynthetic genes, and induces GA-deactivating and ABA-biosynthetic genes. The magnitude of the BL influence over the hormone-related transcriptional profile is also dependent upon CRY1a, highlighting the complex interplay between light and hormonal pathways. These results contribute to a better understanding of BL-induced events behind the photoregulation of tomato seed germination.
Keywords: ABA; Gibberellin (GA); Light signaling; Photoreceptors; Solanum lycopersicum